A NOTE ON APPLICATION OF HILLS' PROCEDURE FOR GROWTH~ CURVE ANALYSIS OF INDIAN MAJOR CARP, LABEO ROHITA (HAM.), DURING THE GONODAL DEVELOPMENT PERIOD AT SHILLONG, MEGHALAYA - Sarma, D.; Day, S.; Dutta, A. (Journal of Indian Fisheries Association, 2015)
The present study deals with the lengthincrement data of 15 adult Labeo rohita(Ham.) over a period of five months by theapplicatin of finite difference method at analtitude of 1496 m above mean sea level atShilllong, Meghalaya.The technique of repeated measurementhas been used frequently to analysebiological growth data (Anderson, 1978).Experiments of this type have broadapplication, especially in life and socialsciences. The alternative approach is thetime-series anaylsis including autoregression (Rosner and Munoz, 1988). Basuand Bhattacharya (1996) applied Hills'(1968) procedure for growth-curve analysisof a freshwater major carp ofindia duringthe early stages of development. Thismethodology has predictive capabilities onshort and long term bases. The proceduremay be summarized in the following lines: